OPTIMALISASI PENYERAPAN REALISASI PENGGUNAAN DANA DAU (DANA ALOKASI UMUM) PERUNTUKAN PADA DINAS KESEHATAN KABUPATEN BENGKALIS TAHUN 2024: OPTIMALISASI PENYERAPAN REALISASI PENGGUNAAN DANA DAU (DANA ALOKASI UMUM) PERUNTUKAN PADA DINAS KESEHATAN KABUPATEN BENGKALIS TAHUN 2024 - maulia, hafizhah; Jasrida, Ermanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The Bengkalis Regency Health Office plays a crucial role in supporting efforts to improve public health services. The office has a significant responsibility to design and implement health programs tailored to community needs. This is a serious concern, given its impact on the implementation of much-needed health programs and the delay in the subsequent disbursement of the General Allocation Fund (DAU) due to the failure to achieve the target realization percentage. The design used was qualitative research, focused on monitoring, analyzing, and strategically managing the health budget. Activities included orientation and observation of the organizational structure, interviews with key informants, planning analysis using the Fishbone method, and the development of a data-driven intervention plan. The research resulted in the development of an intervention plan and the formation of a standard operating procedure (SOP) team comprising regional government agencies (SKPD), financial experts, and internal auditors at the Bengkalis Health Office. Keywords: Optimization of Absorption, Realization, General Allocation Fund (DAU)